Simple and Robust Analysis of Cefuroxime in Human Plasma by LC-MS/MS: Application to a Bioequivalence Study - Xingjiang Hu; Mingzhu Huang; Jian Liu; Junchun Chen; Jianzhong Shentu (Hindawi Limited, 2014)
A simple, robust LC-MS/MS assay for quantifying cefuroxime in human plasma was developed. Cefuroxime and tazobactam, as internal standard (IS), were extracted from human plasma by methanol to precipitate protein. Separation was achieved on a Zorbax SB-Aq (4.6×250 mm, 5 μm) column under isocratic conditions. The calibration curve was linear in the concentration range of 0.0525-21.0 μg/mL (r=0.9998). The accuracy was higher than 90.92%, while the intra- and interday precision were less than 6.26%. The extraction procedure provides recovery ranged from 89.44% to 92.32%, for both analyte and IS. Finally, the method was successfully applied to a bioequivalence study of a single 500 mg dose of cefuroxime axetil in 22 healthy Chinese male subjects under fasting condition. Bioequivalence was determined by calculating 90% Cls for the ratios of Cmax, AUC0-t, and AUC0-∞ values for the test and reference products, using logarithmic transformed data. The 90% Cls for the ratios of Cmax (91.4%~104.2%), AUC0-t (97.4%~110.9%), and AUC0-∞ (97.6%~111.1%) values were within the predetermined range. It was concluded that the two formulations (test for capsule, reference for tablet) analyzed were bioequivalent in terms of rate and extent of absorption and the method met the principle of quick and easy clinical analysis.